ADOLESCENTS WITH BEHAVIORAL PROBLEMS: PERSONALITY, QUALITY OF LIFE AND SOCIAL HEALTH CARE - S. Ya. Volgina; A. S. Kondrat'ev; V. Yu. Al'bitskii; N. V. Ustinova; R. F. Shavaliev (Вопросы современной педиатрии)
Deviant behavior of adolescents is a serious social problem in today's society because of the significant prevalence of this phenomenon. Authors present the results of the study of adolescents with behavioral problems. Aim: optimization of medical and social care for adolescents with behavioral problems. Patients and methods: the authors studied the incidence of this condition among children aged from 15 to 17 years using the software package «SOC/PEDIATRIA-2». The features of the personality structure of adolescents with deviant behavior were revealed using the adopted Russian short version of MMPI-MINI-MULT. Demographic and social characteristics of the families of adolescents were assessed. SF-36 questionnaire was applied for the quality of life assessment of the studied category. Results: increasing morbidity among adolescents was revealed due to various reasons: economic, medical and social. The study allowed to develop personal characteristics of the criteria in order to timely identify adolescents with accentuated and psychopathological features. The characteristics of quality of life were used as criteria of health care for adolescents with behavioral problems. The measures for the prevention and correction of deviant behavior among adolescents were proposed, including intersectoral integration and active participation of family in the process of rehabilitation. Conclusions: it is necessary to identify adolescents with deviant behavior timely, followed by a set of measures to provide them with health and social care to protect their health.